2018
DOI: 10.1177/1045389x18770740
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and tribological characteristics of a disc-type magnetorheological brake operated by the shear mode

Abstract: In this article, thermal characteristics and tribological properties of a disk-type magnetorheological fluid–based brake are investigated under various brake operating conditions such as different working gaps. In order to achieve this goal, a theoretical analysis of the heating and heat dissipation of the magnetorheological brake is first performed and then the transient temperature behaviors of the magnetorheological brake are investigated through simulation works associated with the finite element method. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…The most frequent uses of ER and MR fluids are in devices such as clutches and brakes (Olszak et al, 2016a;Raju et al, 2016;Gao et al, 2017). To achieve the assumed characteristics of clutches and brakes with ER and MR fluids, their architectures are taken into consideration by analyzing the shape and position of working space (Avraam et al, 2010), the way of producing the electric or magnetic field (Takesue et al, 2003;Böse et al, 2013;Sohn et al, 2018) as well as thermal working conditions (Chen et al, 2015;Song et al, 2018). Additionally taken into consideration are the smart fluids used for construction of clutches and brakes with ER and MR, mainly their composition (Sarkar and Hirani, 2013;Kumbhar et al, 2015;Mangal et al, 2016) and durability (Olszak et al, 2016b;Kim et al, 2017;Ziabska et al, 2017).…”
Section: Literature Studymentioning
confidence: 99%
“…The most frequent uses of ER and MR fluids are in devices such as clutches and brakes (Olszak et al, 2016a;Raju et al, 2016;Gao et al, 2017). To achieve the assumed characteristics of clutches and brakes with ER and MR fluids, their architectures are taken into consideration by analyzing the shape and position of working space (Avraam et al, 2010), the way of producing the electric or magnetic field (Takesue et al, 2003;Böse et al, 2013;Sohn et al, 2018) as well as thermal working conditions (Chen et al, 2015;Song et al, 2018). Additionally taken into consideration are the smart fluids used for construction of clutches and brakes with ER and MR, mainly their composition (Sarkar and Hirani, 2013;Kumbhar et al, 2015;Mangal et al, 2016) and durability (Olszak et al, 2016b;Kim et al, 2017;Ziabska et al, 2017).…”
Section: Literature Studymentioning
confidence: 99%
“…However, recent advances in the mechanical, electrical and chemical characteristics of these fluids have permitted the development of novel electromechanical devices, which have been successfully utilised to optimise the function of many commercial automotive, aerospace and structural systems. The majority of these devices have employed the fluids in a simple flow [13,14] or shear mode [15,16] of operation, where the fluid flow is controlled in the former, while the fluid shearing is controlled in the latter. Furthermore, an alternative arrangement, squeeze mode, in which the fluid is subjected to compressive and tensile stresses, has been identified for small motion isolation [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…They investigated the effect of many main factors, such as the slip power [12], input current [13] and cooling conditions [13,14,15], on the temperature variation of MRFs. Besides, Song et al [16] investigated the slip differential heat and heat dissipation of the magnetorheological brake under different working gaps. The results of the research indicated that the temperature caused by the slip differential heat is higher under the smaller working gap contrast to the larger gap [16].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Song et al [16] investigated the slip differential heat and heat dissipation of the magnetorheological brake under different working gaps. The results of the research indicated that the temperature caused by the slip differential heat is higher under the smaller working gap contrast to the larger gap [16]. Wang et al [17] studied the effect of the slip differential heat and heat dissipation on the torque of a high-torque squeezing magnetorheological brake and obtained the relationship between the torque and temperature by conducting a temperature–torque performance experiment [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation